The sort handbook for writers - Schiffhorst, Gerald J. (McGraw - Hill, 1997)
One of the original concise guides to the essentials of composition, this compact handbook not only provides students with a handy grammar reference, but also with an effective guide to the composing process. This streamlined new edition features a new comb binding with easy-to-use tabs. It continues to provide quick accessible information about grammar, usage, and stylistic considerations, and now includes updated coverage on electronic documentation and a new section on editing for ESL problems.